TÍNH CHẤT QUANG CỦA MÀNG PHỦ POLYVINYL PYROLIDON (PVP) BỌC PHỦ HẠT NANO ZnS:Mn TỔNG HỢP BẰNG PHƯƠNG PHÁP HOÁ HỌC - Thi, Trần Minh; Hiền, Nguyễn Thị; Trung, Vũ Quốc (Vietnam Journal of Science and Technology, 2012)
THE OPTICAL PROPERTIES OF THE POLYVINYL PYRROLIDONE (PVP) CAPPED ZnS:Mn NANOCRYSTALLINE SYNTHESIZED BY CHEMICAL METHOD This study has been carried out on the optical properties of PVP (polyvinyl pyrrolidone) capped ZnS:Mn nanocrystalline powders and thin film. The influence of the concentration of PVP capping polymer on the optical properties of the PVP capped ZnS:Mn nanocrystalline thin films synthesized by the wet chemical method with the optimal Mn concentration was studied. The microstructures of the samples were investigated by the X-ray diffraction (XRD) patterns, the atomic absorption spectroscopy AAS-600, and transmission electron microscopy (TEM). The results showed that the prepared samples belonged to the sphalerite structure with the average particle size of about 2 - 3 nm. The optical properties of samples were studied by measuring photoluminescence (PL) spectra in the wavelength range from 325 nm to 700 nm at 300 K. The luminescence spectra of PVP showed the blue emissiom with maximum of 425 nm. While the PVP coating did not affect the microstructure of ZnS:Mn nanomaterial, the PL spectra of the samples were found to be affected by the PVP concentration.